2018
DOI: 10.1021/acs.jnatprod.7b00807
|View full text |Cite
|
Sign up to set email alerts
|

Can Stereoclusters Separated by Two Methylene Groups Be Related by DFT Studies? The Case of the Cytotoxic Meroditerpenes Halioxepines

Abstract: QM/NMR-DFT (quantum mechanics combined with nuclear magnetic resonance parameters calculated by density functional theory approximations) studies allowed us to link two stereoclusters separated by two methylene groups present in the new meroditerpenes halioxepine B (2) and halioxepine C (3) and the known halioxepine (1), isolated from two Indonesian sponges of the genus Haliclona (Reniera). DP4 and DP4+ probabilities were used to discriminate the two diastereotopic arrangements of the two stereoclusters, whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The development of quantum chemical methods for calculating NMR chemical shifts has led to a significant number of studies that combine experimental chemical shifts with computations [ 39 , 40 , 41 , 42 ]. Nevertheless, a few examples of organic molecules whose structures have been determined by both computations of NMR chemical shifts in solution and X-ray structures have been published [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The development of quantum chemical methods for calculating NMR chemical shifts has led to a significant number of studies that combine experimental chemical shifts with computations [ 39 , 40 , 41 , 42 ]. Nevertheless, a few examples of organic molecules whose structures have been determined by both computations of NMR chemical shifts in solution and X-ray structures have been published [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…A significant number of studies have been published that combine experimental NMR chemical shifts with computations [ 24 , 25 , 26 , 27 , 28 ] and investigating high resolution structures in solution [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. When we consider the importance of calculations of NMR parameters in structural chemistry, it is surprising that no applications in lipid research have so far been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The development of quantum chemical methods for calculating NMR parameters, with emphasis on chemical shifts, as well as advances in computational techniques and computer power, have led to an increasing number of studies that combine calculation with experiment [16,17,18,19,20]. Several examples of using computed NMR chemical shifts to confirm proposed structures or to aid the reassignment of structures can be found in the literature [20,21,22,23,24,25]. To date, however, only a handful examples of organic molecules whose structures have been determined by both computation of NMR chemical shifts in solution and X-ray were reported [26,27,28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%